Multimeter Measuring Tool Application as Alternative Method of Resistance Characteristics Discern Between the Sauce brand "abc" Sauce with brand "dena" - Nurrohmah, Salisa; Rahmah, Gebrina; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
The sauce is an ingredient in cooking or food complement. The materials used is chili or tomato sauce. Use of the basic ingredients in the sauce affect the physical quantities of the dressing. One of the physical quantities that can be measured is resistance. Resistance can be defined as the amount that inhibits electrical current. The purpose of this study was to determine the resistance characteristics of materials ABC sauce and dressing materials Dena. Different from the base material, the resistance value will be different sauces. By using Analog Multimeter and perform measurements five times, found a resistance value of (4.6; 4.6; 4.8; 4.8; and 4.7) ? for ABC dressing material and material obtained resistance value Dena sauce by (4.3; 4.4; 4.4; 4.3; and 4.5) ? with th e volume of each sauce is ± 10ml.